Degradation of EPDM and FPM elastomers irradiated at very high dose rates in mixed gamma and neutron fields. Issue 12 (6th October 2019) - Ferrari, Matteo; Pandini, Stefano; Zenoni, Aldo; Donzella, Giorgio; Battini, Davide; Avanzini, Andrea; Salvini, Andrea; Zelaschi, Fabio; Andrighetto, Alberto; Bignotti, Fabio
Abstract : Elastomers are widely used in radioactive environments, where ionizing radiations induce a deterioration of their properties due to degradative phenomena occurring in the polymer structure. Their radiation resistance is usually assessed using γ‐rays and relatively low dose rates, but in actual applications, they are often exposed to mixed radiation fields and higher dose rates. Ethylene propylene diene monomer (EPDM) is known for its excellent resistance to γ‐rays but absorbs a larger dose by neutron interactions than fluoroelastomer (FPM). In this work, EPDM and FPM were irradiated in mixed neutron and gamma fields, using high dose rates (from 22 to 700 kGy h −1 ) and total absorbed doses between 0.2 and 3.5 MGy. The effects of irradiation were assessed by swelling tests, differential scanning calorimetry analysis and dynamic mechanical thermal analysis, and tensile tests. The results show that, even if irradiations were carried out in air, degradation took place under nonoxidative conditions owing to the high dose rates employed. Under such conditions, crosslinking is the dominant radiation‐induced reaction in both elastomers. Moreover, material degradation seems to be influenced mostly by the total absorbed dose and not by the type of radiation. Contrary to what observed at the lower dose rates employed with γ‐rays, major dose rate effects are not observed. POLYM. ENG. SCI., 59:2522–2532, 2019. © 2019 Society of Plastics Engineers